2004
DOI: 10.1074/jbc.m402902200
|View full text |Cite
|
Sign up to set email alerts
|

Nucling Recruits Apaf-1/Pro-caspase-9 Complex for the Induction of Stress-induced Apoptosis

Abstract: Nucling is a novel protein isolated from murine embryonal carcinoma cells with an up-regulated expression during cardiac muscle differentiation. We show here that Nucling was up-regulated by proapoptotic stimuli and important for the induction of apoptosis after cytotoxic stress. We further demonstrated that overexpressed Nucling was able to induce apoptosis. In Nucling-deficient cells, the expression levels of Apaf-1 and cytochrome c, which are the major components of an apoptosis-promoting complex named apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…Nucling, a protein of unknown function that is upregulated in cardiac muscle differentiation, has been proposed to act as a carrier for Apaf-1 nuclear uptake, since NuclingÀ/À MEFs do not show Apaf-1 relocalisation to the nucleus after UV irradiation. 30 These cells are also resistant to UV-induced cell death, suggesting that Apaf-1 might exert a proapoptotic function in the nucleus, at least in some apoptosis model systems.…”
Section: Apaf-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Nucling, a protein of unknown function that is upregulated in cardiac muscle differentiation, has been proposed to act as a carrier for Apaf-1 nuclear uptake, since NuclingÀ/À MEFs do not show Apaf-1 relocalisation to the nucleus after UV irradiation. 30 These cells are also resistant to UV-induced cell death, suggesting that Apaf-1 might exert a proapoptotic function in the nucleus, at least in some apoptosis model systems.…”
Section: Apaf-1mentioning
confidence: 99%
“…29 Recent data, however, suggest that Apaf-1 might migrate to the nucleus also in mammalian cells during stress-induced apoptosis (e.g. Sakai et al 30 ). Nuclear translocation of Apaf-1 seems to be an early event preceding mitochondrial cytochrome C release.…”
Section: Apaf-1mentioning
confidence: 99%
“…Animal experiments and tissue preparation WT and Nucling-KO mice were prepared as described (14,15). Age-matched male mice between 8 and 12 weeks old were used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we have also reported that Nucling mediates apoptosis by inhibiting the expression of galectin-3 (16), an anti-apoptotic factor, through interference with NF-kB signalling pathway (17). Nucling is also associated with the apoptosome pathway by recruiting the Apaf-1/procaspase-9 complex following cytotoxic stress (14). However, Nucling-KO mice did not show any developmental abnormalities common to Apaf-1-or caspase-deficient mice because of the defect in apoptosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation